Efficacy and safety of ascending doses of moxidectin against Strongyloides stercoralis infections in adults: a randomised, parallel-group, single-blinded, placebo-controlled, dose-ranging, phase 2a trial. Issue 8 (August 2021) - Hofmann, Daniela; Sayasone, Somphou; Sengngam, Khanpaseuth; Chongvilay, Bounthunh; Hattendorf, Jan; Keiser, Jennifer
Summary: Background: Strongyloidiasis represents a major public health issue, particularly in resource-limited countries. Preliminary studies suggest that moxidectin might serve as an alternative to the only available treatment option, ivermectin. We aimed to evaluate the efficacy and safety of ascending doses of moxidectin in Strongyloides stercoralis -infected patients. Methods: We did a randomised, parallel-group, single-blinded, placebo-controlled, dose-ranging, phase 2a trial in four villages in northern Laos. Eligible adults (aged 18–65 years) with S stercoralis infection intensities of at least 0·4 larvae per g of stool in at least two stool samples were randomly assigned (1:1:1:1:1:1:1) by use of computerised, stratified, block randomisation into seven treatment groups: 2 mg of moxidectin, 4 mg of moxidectin, 6 mg of moxidectin, 8 mg of moxidectin, 10 mg of moxidectin, 12 mg of moxidectin, or placebo. Participants and primary outcome assessors were masked to treatment allocation, but study site investigators were not. Participants received a single oral dose of their allocated dose of moxidectin in 2 mg tablets, or four placebo tablets. Three stool samples were collected at baseline and two stool samples were collected 28 days after treatment from each participant. A Baermann assay was used to quantify S stercoralis infection and Kato–Katz thick smears were used to qualitatively identify coinfections with additional helminths species. The primary endpoint was cure rate against S stercoralis and was analysed in an available case analysis set, defined as all randomly assigned participants with primary endpoint data. Predicted cure rates and associated CIs were estimated with hyperbolic Emax models. Safety was evaluated in the intention-to-treat population. This trial is registered at ClinicalTrials.gov, NCT04056325, and is complete. Findings: Between Nov 27, 2019, and March 15, 2020, 785 adults were screened for trial eligibility. Of these, 223 participants were randomly assigned to treatment groups and 209 completed the study and were analysed for the primary outcome. 2 mg of moxidectin had a predicted cure rate of 75% (95% CI 59–87; 22 [73%] of 30 cured) against S stercoralis compared with a predicted cure rate of 14% (5–31; four [14%] of 29 cured) for placebo. With escalating doses, the probability of cure increased from 83% (95% CI 76–88; 26 [90%] of 29 cured) at 4 mg to 86% (79–90; 27 [84%] of 32 cured) at 6 mg, and to 87% (80–92; 24 [83%] of 29 cured) at 8 mg, levelling off at 88% (80–93; 29 [97%] of 30 cured) at 10 mg and 88% (80–93; 26 [87%] of 30 cured) at 12 mg. Moxidectin was well tolerated across all treatment groups, with no serious adverse events being recorded and all reported symptoms being classified as mild. Interpretation: 4–12 mg of moxidectin showed promising tolerability and efficacy profiles in the treatment of S stercoralis infections in adults. Because 8 mg of moxidectin is used for the treatment of onchocerciasis and has been evaluated for other helminth infections, we recommend this dose for phase 2b and phase 3 trials of strongyloidiasis therapy. Funding: Fondazione Adiuvare.